2017
DOI: 10.1186/s12933-017-0603-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelial nitric oxide in the anti-restenotic effects of liraglutide in a mouse model of restenosis

Abstract: BackgroundPrevious animal studies have shown that glucagon-like peptide-1 receptor agonists (GLP-1RAs) suppress arterial restenosis, a major complication of angioplasty, presumably through their direct action on vascular smooth muscle cells. However, the contribution of vascular endothelial cells (VECs) to this process remains unknown. In addition, the potential interference caused by severe hyperglycemia and optimal treatment regimen remain to be determined.MethodsNine-week-old male C57BL6 (wild-type) and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 58 publications
(72 reference statements)
1
43
0
Order By: Relevance
“…Exenatide has direct vascular protective effects on endothelial cells and modulates vascular inflammation [22][23][24]. Liraglutide is a GLP-1-derived peptide, and it has been shown that liraglutide could also enhance endothelial function and suppress endothelial inflammation and atherosclerosis in animal models [25][26][27][28]. Lixisenatide has been evaluated in broad clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Exenatide has direct vascular protective effects on endothelial cells and modulates vascular inflammation [22][23][24]. Liraglutide is a GLP-1-derived peptide, and it has been shown that liraglutide could also enhance endothelial function and suppress endothelial inflammation and atherosclerosis in animal models [25][26][27][28]. Lixisenatide has been evaluated in broad clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, NO inhibits proliferation and migration of VSMCs processes that contribute to the development of atherosclerotic plaques 29 . We previously reported that liraglutide treatment increases NO levels in plasma and phosphorylated endothelial NO synthase levels in the aorta 18 . In addition, liraglutide treatment suppresses peripheral arterial remodeling in mouse models, and this effect is completely abolished by inhibiting NO synthase.…”
Section: Discussionmentioning
confidence: 96%
“…Blood pressure and pulse rate were measured using the tail-cuff method, as previously described Model MK-2000ST ; Muromachi Kikai, Tokyo, Japan 18 .…”
Section: Blood Pressure and Pulse Rate Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these drugs can also directly target vascular cells finally resulting in reduced atherogenesis. Preclinical data suggested that liraglutide can suppress restenosis via endothelial nitric oxide release in a mouse model of femoral artery wire injury in presence of severe hyperglycaemia . In addition, liraglutide decreased the progression of atherogenesis, contributing to plaque stability and endothelial function both in preclinical and clinical studies .…”
Section: Direct Evidences For New Anti‐diabetic Drugs Against CV Diseasementioning
confidence: 99%